2015
DOI: 10.1007/s00520-015-2613-0
|View full text |Cite
|
Sign up to set email alerts
|

Post-allogeneic Hematopoietic Stem Cell Transplantation (HSCT) changes in inorganic salivary components

Abstract: Recent studies have considered the qualitative and quantitative assessment of salivary flow, as well the biochemical components of saliva, as possible biomarkers that might contribute to the pathogenesis of chronic graft-versus-host disease (cGHVD) in hematopoietic stem cell transplantation (HSCT) patients. The aim of this study was to evaluate prospectively the inorganic salivary status at different periods of allogeneic HSCT. Saliva collection and oral examination were performed prior to the HSCT, ​between d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
30
3
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(39 citation statements)
references
References 28 publications
1
30
3
2
Order By: Relevance
“…Our study cannot thoroughly confirm this previous finding. Likewise, a couple of studies with a 100‐day follow‐up did not notice any changes in DMFT index or an increase in new dental caries lesions in this short follow‐up period . However, in this study, hyposalivation was observed to be associated with progression towards a higher DMFT index score.…”
Section: Discussioncontrasting
confidence: 54%
See 1 more Smart Citation
“…Our study cannot thoroughly confirm this previous finding. Likewise, a couple of studies with a 100‐day follow‐up did not notice any changes in DMFT index or an increase in new dental caries lesions in this short follow‐up period . However, in this study, hyposalivation was observed to be associated with progression towards a higher DMFT index score.…”
Section: Discussioncontrasting
confidence: 54%
“…Only a few studies exist on the oral health of adult subjects pre‐ and post‐HSCT. These studies suggest hyposalivation to be common and oral health to deteriorate after the HSCT . Additionally, there are no studies on the effects of hyposalivation or the most common oral infections caries and periodontitis on survival post‐HSCT.…”
Section: Introductionmentioning
confidence: 99%
“…Most other studies measuring salivary flow rate after HSCT found a decrease in salivary flow rate (Amaral et al., ; Avivi et al., ; Boer, Correa, Tenuta, Souza, & Vigorito, ; Elad et al., ; Nagler, Barness‐Hadar, Lieba, & Nagler, ). However, one study found no changes in UWS flow rate in autologous HSCT patients, while a study in allogeneic patients showed an increase in UWS flow rate 8‐10 days after HSCT (Avivi et al., ; Boer et al., ). This increase might be related to dysphagia resulting in an increased resting volume of saliva as suggested by the authors (Boer et al., ).…”
Section: Discussionmentioning
confidence: 93%
“…However, one study found no changes in UWS flow rate in autologous HSCT patients, while a study in allogeneic patients showed an increase in UWS flow rate 8‐10 days after HSCT (Avivi et al., ; Boer et al., ). This increase might be related to dysphagia resulting in an increased resting volume of saliva as suggested by the authors (Boer et al., ).…”
Section: Discussionmentioning
confidence: 99%
“…The alterations in the salivary proteome among proteins involved in innate and acquired immunity are consistent with the clinical features of oral cGVHD, in particular patient susceptibility to bacterial and viral infections[4,18]. Changes in inorganic salivary components, especially Na + and Cl - ions and inorganic phosphate, also occur in concert with cGVHD onset, correlating with hyposalivation and damage to the salivary glands[82,83]. …”
Section: Chronic Gvhd Biomarkersmentioning
confidence: 90%